Sodium-supplementing type layered oxide sodium battery positive electrode material as well as preparation method and application thereof
By preparing sodium-enriched layered oxide sodium electropositive electrode material, using the combination of sodium salt and S and C, the problem of improving the circulation performance of the positive electrode material in the prior art is solved, high specific capacity and good rate performance are achieved, and commercialized potential.
Patent Information
- Application Number
- CN202411511039.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-10
AI Technical Summary
The existing transition metal oxide positive electrode materials are difficult to achieve improvement in cycling performance under the conditions of ensuring good specific capacity and rate performance, which limits the performance improvement of sodium ion batteries.
The preparation method of sodium-enhancing layered oxide sodium electropositive electrode material is adopted. By obtaining the layered oxide and mixing it with sodium salt and sintering, then co-grinding with sulfur (S) and carbon (C) mixture, the As a coating agent and S and C as surfactants, the formed materials can replenish lost sodium ions during chemical synthesis and cyclic charge and discharge, improve electronic conductivity and improve rate performance.
The high specific capacity and good cycle performance of sodium electropositive electrode materials have been achieved, and the rate performance has been significantly improved, with good commercial prospects.
Smart Images

Figure CN119284982A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery positive electrode material preparation, and in particular to a sodium-supplemented layered oxide sodium battery positive electrode material, and a preparation method and application thereof. Background Art
[0002] Due to the advantages of low price and wide distribution of sodium resources, the research of sodium-ion batteries and their key electrode materials has attracted widespread attention in recent years. However, compared with lithium, the ionic radius of sodium is much larger, which makes its migration speed in sodium storage materials too slow, which seriously limits the improvement of sodium-ion battery rate performance and the expression of sodium storage capacity. In addition, the higher relative atomic mass of sodium also theoretically limits the energy density of sodium-ion batteries.
[0003] At present, the cathode materials used in sodium-ion batteries mainly include transition metal oxide systems, polyanion compounds (phosphate systems, fluorophosphate systems, NASICON structures) and Prussian blue systems. Among them, transition metal oxide cathode materials, with their high voltage platform and excellent rate performance, have attracted widespread attention and research, but the cycle performance of this type of material is still relatively low. How to achieve improved cycle performance while ensuring good specific capacity and rate performance needs to be solved urgently. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the existing transition metal oxide positive electrode materials are difficult to achieve improved cycle performance under the conditions of good specific capacity and rate performance, thereby providing a sodium-supplemented layered oxide sodium battery positive electrode material and its preparation method and application that solve the above problem.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a sodium-supplemented layered oxide sodium positive electrode material comprises: obtaining a layered oxide; mixing the layered oxide with a sodium salt and sintering the mixture to obtain a sintered material; and mixing the sintered material with a mixture of S and C and co-grinding the mixture to obtain the material.
[0007] Preferably, the chemical formula of the layered oxide is Na a Ni x Fe y Mn 1-x-y O2; among which, 0.65≤a≤0.72, 0<x≤0.5, 0<x≤0.5, x+y<1.
[0008] Preferably, the mass ratio of the layered oxide to the sodium salt is 100:(0.5-1.5), preferably 100:1;
[0009] And / or, the mass ratio of S to C in the S and C mixture is (0.5-2):1;
[0010] And / or, the mass ratio of the sintering material to the S, C mixture is (9-100):1;
[0011] and / or, the sodium salt comprises sodium silicate;
[0012] And / or, S in the S, C mixture comprises sulfur;
[0013] And / or, C in the S, C mixture includes at least one of carbon black, carbon fiber, and carbon nanotubes.
[0014] Preferably, the sintering temperature is 650-750°C, preferably 700°C;
[0015] And / or, the sintering treatment time is 5-7 hours, preferably 6 hours;
[0016] And / or, the atmosphere of the sintering treatment is air and / or oxygen.
[0017] Preferably, the co-grinding process is a ball milling process.
[0018] Preferably, the ball-to-material ratio of the ball milling process is (10-50):1;
[0019] And / or, the rotation speed of the ball milling treatment is 200-500r / min;
[0020] And / or, the ball milling treatment is performed for 2-10 hours.
[0021] Preferably, the process of obtaining the layered oxide comprises: weighing a nickel-iron-manganese precursor material and a sodium source according to the stoichiometric ratio of the layered oxide, mixing them, and performing heat treatment to obtain the layered oxide.
[0022] Preferably, the sodium source comprises sodium carbonate;
[0023] And / or, the heat treatment temperature is 950-1050°C, preferably 1000°C;
[0024] And / or, the heat treatment duration is 10-14 hours, preferably 12 hours;
[0025] And / or, the atmosphere of the heat treatment is air and / or oxygen.
[0026] The present invention also provides a sodium-supplemented layered oxide sodium-electric positive electrode material, which is prepared by the above-mentioned method for preparing the sodium-supplemented layered oxide sodium-electric positive electrode material.
[0027] The present invention also provides the use of the above-mentioned sodium-supplementing layered oxide sodium-electric positive electrode material in a sodium ion battery.
[0028] In the present invention, the sintered material is directly mixed with the S and C mixture and co-grinded, and the sodium-supplemented layered oxide sodium positive electrode material is obtained without subsequent heating treatment.
[0029] The technical solution of the present invention has the following advantages:
[0030] A method for preparing a sodium-supplemented layered oxide sodium positive electrode material comprises: obtaining a layered oxide; mixing the layered oxide with a sodium salt and sintering the mixture to obtain a sintered material; mixing the sintered material with an S-C mixture and co-grinding the mixture to obtain a sintered material. The present invention uses sodium salt as a coating agent and an S-C mixture as a surfactant, so that the formed positive electrode material can replenish the lost sodium ions in a timely manner during chemical synthesis and cyclic charge and discharge; in addition, the C in the S-C mixture improves the electronic conductivity of the material, thereby significantly improving the rate performance of the material, and the S in the S-C mixture reacts with the sodium salt at the electrode end under the electrochemical action during the battery activation stage, prompting the Na ions in the sodium salt to participate in the charge transfer, thereby further compensating for the loss of Na ions in the chemical synthesis stage of the material. Based on the above technical means, the sodium-supplemented sodium positive electrode material prepared by the present invention not only has a high specific capacity, but also exhibits good cycle performance and rate performance, and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a SEM morphology of the sodium-supplemented layered oxide sodium positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0034] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0035] Example 1
[0036] This embodiment provides a method for preparing a sodium-supplemented layered oxide sodium positive electrode material, and the specific steps are as follows:
[0037] 1) Weigh the precursor Ni according to the ratio of sodium to 0.68 0.30 Fe 0.35 Mn 0.35 (OH)2 and sodium carbonate were mixed in a high-speed mixer and then heated in a box furnace at 1000°C in an air atmosphere (5m 3 / h), sintered for 12h, and then crushed to obtain layered oxide Na 0.68 Ni 0.30 Fe 0.35 Mn 0.35 O2;
[0038] 2) Weigh 500 g of the layered oxide in step 1) and 5 g of Na2SiO3 and add them into a high-speed mixer to mix them evenly. Then, heat them in a box furnace at 700°C in an air atmosphere (5 m 3 / h), sintering for 6h to carry out sintering coating, after the sintering is completed, the sintering material is obtained;
[0039] 3) According to the mass ratio of 9:1, the sintered material in step 2) is mixed with a mixture of S and C (S:C=2:1, S is sulfur, C is carbon fiber) by spheroidal graphite, the ball-to-material ratio is 30:1, the ball milling speed is 400r / min, and the ball milling time is 8h, so as to obtain a sodium-supplemented layered oxide sodium positive electrode material, whose SEM morphology is as follows: Figure 1 shown.
[0040] Example 2
[0041] This embodiment provides a method for preparing a sodium-supplemented layered oxide sodium positive electrode material, and the specific steps are as follows:
[0042] 1) Weigh the precursor Ni according to the ratio of sodium to 0.72 0.3 Fe 0.1 Mn 0.6 (OH)2 and sodium carbonate were mixed in a high-speed mixer and then heated in a box furnace at 1000°C in an air atmosphere (5m 3 / h), sintered for 12h, and then crushed to obtain layered oxide Na 0.72 Ni 0.3 Fe 0.1 Mn0.6 O2;
[0043] 2) Weigh 500 g of the layered oxide in step 1) and 5 g of Na2SiO3 and add them into a high-speed mixer to mix them evenly. Then, heat them in a box furnace at 700°C in an air atmosphere (5 m 3 / h), sintering for 6h to carry out sintering coating, after the sintering is completed, the sintering material is obtained;
[0044] 3) According to a mass ratio of 100:1, the sintered material in step 2) is mixed with a mixture of S and C (S:C=1:1, S is sulfur, and C is carbon nanotubes) by ball-graphite, the ball-to-material ratio is 10:1, the ball milling speed is 500r / min, and the ball milling time is 2h, so as to obtain a sodium-supplemented layered oxide sodium positive electrode material.
[0045] Example 3
[0046] This embodiment provides a method for preparing a sodium-supplemented layered oxide sodium positive electrode material, and the specific steps are as follows:
[0047] 1) Weigh the precursor Ni according to the ratio of sodium to 0.65 0.1 Fe 0.4 Mn 0.5 (OH)2 and sodium carbonate were mixed in a high-speed mixer and then heated in a box furnace at 1000°C in an air atmosphere (5m 3 / h), sintered for 12h, and then crushed to obtain layered oxide Na 0.65 Ni 0.1 Fe 0.4 Mn 0.5 O2;
[0048] 2) Weigh 500 g of the layered oxide in step 1) and 5 g of Na2SiO3 and add them into a high-speed mixer to mix them evenly. Then, heat them in a box furnace at 700°C in an air atmosphere (5 m 3 / h), sintering for 6h to carry out sintering coating, after the sintering is completed, the sintering material is obtained;
[0049] 3) According to a mass ratio of 50:1, the sintered material in step 2) is mixed with a mixture of S and C (S:C=0.5:1, S is sulfur, C is carbon black) by spheroidal graphite, the ball-to-material ratio is 50:1, the ball milling speed is 200r / min, and the ball milling time is 10h, so as to obtain a sodium-supplemented layered oxide sodium positive electrode material.
[0050] Comparative Example 1
[0051] This comparative example provides a method for preparing a sodium-supplemented layered oxide sodium positive electrode material, and the specific steps are as follows:
[0052] 1) 5.0 kg of precursor Ni0.30 Fe 0.35 Mn 0.35 (OH)2 was mixed with 2.0 kg of sodium carbonate in a high-speed mixer and then heated in a box furnace at 1000 °C in an air atmosphere (5 m 3 / h), sintering for 12h, and then crushing to obtain layered oxide;
[0053] 2) Weigh 500 g of the layered oxide in step 1) and 5 g of Na2SiO3 and add them into a high-speed mixer to mix them evenly. Then, heat them in a box furnace at 700°C in an air atmosphere (5 m 3 / h), sintering for 6h for sintering coating, and after the sintering is completed, the sodium-supplemented layered oxide sodium positive electrode material is obtained.
[0054] Comparative Example 2
[0055] This comparative example provides a method for preparing a sodium-supplemented layered oxide sodium positive electrode material, and the specific steps are as follows:
[0056] 1) 5.0 kg of precursor Ni 0.30 Fe 0.35 Mn 0.35 (OH)2 was mixed with 2.0 kg of sodium carbonate in a high-speed mixer and then heated in a box furnace at 1000 °C in an air atmosphere (5 m 3 / h), sintering for 12h, and then crushing to obtain layered oxide;
[0057] 2) According to the mass ratio of 9:1, the layered oxide in step 2) is mixed with a mixture of S and C (S:C=2:1, S is sulfur, C is carbon fiber) by spheroidal graphite, the ball-to-material ratio is 30:1, the ball milling speed is 400r / min, and the ball milling time is 8h, so as to obtain a sodium-supplemented layered oxide sodium positive electrode material.
[0058] Comparative Example 3
[0059] This comparative example provides a method for preparing a sodium-supplemented layered oxide sodium positive electrode material, and the specific steps are as follows:
[0060] 1) 5.0 kg of precursor Ni 0.30 Fe 0.35 Mn 0.35 (OH)2 was mixed with 2.0 kg of sodium carbonate in a high-speed mixer and then heated in a box furnace at 1000 °C in an air atmosphere (5 m 3 / h), sintering for 12h, and then crushing to obtain layered oxide;
[0061] 2) Weigh 500 g of the layered oxide in step 1) and 5 g of Na2SiO3 and add them into a high-speed mixer to mix them evenly. Then, heat them in a box furnace at 700°C in an air atmosphere (5 m 3 / h), sintering for 6h to carry out sintering coating, after the sintering is completed, the sintering material is obtained;
[0062] 3) The sintered material in step 2) is mixed with sulfur in a ball-graphite manner at a mass ratio of 9:1, the ball-to-material ratio is 30:1, the ball milling speed is 400 r / min, and the ball milling time is 8 h, thereby obtaining a sodium-supplemented layered oxide sodium positive electrode material.
[0063] Comparative Example 4
[0064] This comparative example provides a method for preparing a sodium-supplemented layered oxide sodium positive electrode material, and the specific steps are as follows:
[0065] 1) 5.0 kg of precursor Ni 0.30 Fe 0.35 Mn 0.35 (OH)2 was mixed with 2.0 kg of sodium carbonate in a high-speed mixer and then heated in a box furnace at 1000 °C in an air atmosphere (5 m 3 / h), sintering for 12h, and then crushing to obtain layered oxide;
[0066] 2) Weigh 500 g of the layered oxide in step 1) and 5 g of Na2SiO3 and add them into a high-speed mixer to mix them evenly. Then, heat them in a box furnace at 700°C in an air atmosphere (5 m 3 / h), sintering for 6h to carry out sintering coating, after the sintering is completed, the sintering material is obtained;
[0067] 3) The sintered material in step 2) is mixed with carbon nanotubes in a ball-graphite manner at a mass ratio of 9:1, the ball-to-material ratio is 30:1, the ball milling speed is 400 r / min, and the ball milling time is 8 h, thereby obtaining a sodium-supplemented layered oxide sodium positive electrode material.
[0068] Comparative Example 5
[0069] This comparative example provides a method for preparing a sodium-supplemented layered oxide sodium positive electrode material, and the specific steps are as follows:
[0070] 1) 5.0 kg of precursor Ni 0.30 Fe 0.35 Mn 0.35 (OH)2 was mixed with 2.0 kg of sodium carbonate in a high-speed mixer and then heated in a box furnace at 1000 °C in an air atmosphere (5 m 3 / h), sintering for 12h, and then crushing to obtain layered oxide;
[0071] 2) Weigh 500 g of the layered oxide in step 1) and 5 g of Na2SiO3 and add them into a high-speed mixer to mix them evenly. Then, heat them in a box furnace at 700°C in an air atmosphere (5 m 3 / h), sintering for 6h to carry out sintering coating, after the sintering is completed, the sintering material is obtained;
[0072] 3) The sintered material in step 2) was mixed with a mixture of S and C (S:C = 2:1, S is sulfur, C is carbon fiber) in a mass ratio of 9:1, the ball-to-material ratio was 30:1, the ball milling speed was 400r / min, the ball milling time was 8h, and then the sintered material was mixed with a mixture of S and C (S:C = 2:1, S is sulfur, C is carbon fiber) in a box furnace at 700°C and air atmosphere (5m 3 / h), sintering for 6h and then secondary sintering. After the sintering is completed, the sodium-supplemented layered oxide sodium positive electrode material is obtained.
[0073] Test Example 1
[0074] The sodium positive electrode materials obtained in the above examples and comparative examples were made into batteries. The specific steps were as follows: 95 (sodium positive electrode material): 2.5 (polytetrafluoroethylene (PVDF)): 2.5 (conductive carbon black SP) were homogenized and coated to form pole pieces. The coating surface density was 12.5 mg / cm 2 , using metallic sodium as the counter electrode, glass fiber as the separator, and 1 mol / L NaPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio 1:1) solution as the electrolyte, to assemble a CR2032 button cell.
[0075] The prepared battery was placed in a blue electric test system for electrical performance testing, with a voltage range of 2.5-4.0V, to test its 0.1C charge-discharge specific capacity and initial efficiency, and to test its 50-cycle cycle retention rate at a charge-discharge rate of 1C. The test results are shown in Table 1.
[0076] Table 1
[0077]
[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a sodium-supplemented layered oxide sodium positive electrode material, characterized in that: include: Obtaining layered oxides; mixing the layered oxides with sodium salts and sintering them to obtain sintered materials; The sintered material is mixed with the S and C mixture and then co-grinded to obtain the product.
2. The preparation method according to claim 1, characterized in that: The chemical formula of the layered oxide is Na a Ni x Fe y Mn 1-x-y O2; among which, 0.65≤a≤0.72, 0<x≤0.5, 0<x≤0.5, x+y<1.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the layered oxide to the sodium salt is 100:(0.5-1.5), preferably 100:1; And / or, the mass ratio of S to C in the S and C mixture is (0.5-2):1; And / or, the mass ratio of the sintering material to the S, C mixture is (9-100):1; and / or, the sodium salt comprises sodium silicate; And / or, S in the S, C mixture comprises sulfur; And / or, C in the S, C mixture includes at least one of carbon black, carbon fiber, and carbon nanotubes.
4. The preparation method according to any one of claims 1 to 3, characterized in that The sintering temperature is 650-750°C, preferably 700°C; And / or, the sintering treatment time is 5-7 hours, preferably 6 hours; And / or, the atmosphere of the sintering treatment is air and / or oxygen.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The co-grinding process is a ball milling process.
6. The preparation method according to claim 5, characterized in that: The ball-to-material ratio of the ball milling process is (10-50):1; And / or, the rotation speed of the ball milling treatment is 200-500r / min; And / or, the ball milling treatment is performed for 2-10 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The process of obtaining the layered oxide includes: weighing a nickel-iron-manganese precursor material and a sodium source according to the stoichiometric ratio of the layered oxide, mixing them evenly, and performing heat treatment to obtain the layered oxide.
8. The preparation method according to claim 7, characterized in that: The sodium source includes sodium carbonate; And / or, the heat treatment temperature is 950-1050°C, preferably 1000°C; And / or, the heat treatment duration is 10-14 hours, preferably 12 hours; And / or, the atmosphere of the heat treatment is air and / or oxygen.
9. A sodium-supplemented layered oxide sodium positive electrode material, characterized in that: The material is prepared by the method for preparing the sodium-supplemented layered oxide sodium positive electrode material according to any one of claims 1 to 8.
10. Use of the sodium-supplemented layered oxide sodium-electric cathode material according to claim 9 in sodium-ion batteries.